Twenty years after the big enlargement: Integration within the single market - Paolo Pasimeni (Intereconomics, 2024)
The enlargement of the European Union in 2004 marked a significant milestone in the history of European integration, bringing ten new member states into the Union. This paper provides a comprehensive analysis of the economic impact of this enlargement two decades later. Drawing from the economic literature and descriptive analysis, the paper examines both anticipated benefits and realised outcomes. Preceding the enlargement, ex ante analyses projected substantial gains in GDP, trade integration and welfare for both acceding and existing member countries. These expectations were largely met. At the macroeconomic level, the paper shows a significant reduction in trade costs, enhanced trade integration and deepening participation in cross-border value chains within the Single Market. Some challenges remain, however, in terms of social and territorial cohesion in these countries. The lessons learned from this enlargement underscore the continuous nature of integration, beginning with accession preparation and producing tangible effects throughout the process.
Keywords: F15; F53; O52; O57; P33; 330